O estilo do processo de informação gerado no ambiente de uma universidade pública: contribuição para definição da cultura informacional - Alves, Claudio Augusto (2014)
Considering that information permeates all processes means of the various subsystems of an organization it is possible to direct studies to the organizational context, regarding to understand and identify the practices in which individuals deal to information. It is relevant to study how individuals develop behavioral patterns and oriented attitudes toward information, which implies in doing an analysis from a cultural focus. This research discusses the style of information processes produced in a public university, and it has as general goal to analyze the style of information generated in the organizational environment of the Human Resources Department, in Federal University of Campina Grande (DHR UFCG), intending to define the formation of an informational culture. The methodological procedures were defined in quantitative and qualitative approaches, such as exploratory and descriptive research, characterized as a field study. The research universe comprehended a total of 39 members of the referred department. As instruments of data collection were used mixed questionnaire, semistructured interviews and a field diary to record observations. In the organization and analysis of quantitative data, it was adopted simple statistical techniques for tabulation of the percentage achieved with established averages to define the trends.The technique of content analysis was adopted for qualitative analysis in order to achieve the complexity of the object. Both techniques were associated with the triangulation strategy of data, systematized in tables and charts. The results indicate that in a greater and/or lesser degree, the styles of information are generated in the informational process of DRH UFCG. The nature of the styles revealed in the studied department contributes to the formation of an information culture, motivated by values, practices, attitudes, patterns, symbols, assumptions, rules, behaviors and rituals related to the information usage. Styles trends of information indicated the tendency in the current cultural typology in the researched environment, and highlighted the stage of information culture and its weaknesses, allowing subsequent management investments. In order for informational culture becomes increasingly appropriate and positive it is necessary to establish a better organization and operation of information and thus achieve strategic success in the department.